Group Recommendation System for Facebook - Baatarjav, Enkh-Amgalan; Phithakkitnukoon, Santi; Ram Dantu (On the Move to Meaningful Internet Systems: OTM 2008 Workshops, Monterrey, Mexico, November 9-14, 2008. Proceedings, 2008)
Online social networking has become a part of our everyday lives, and one of the popular online social network (SN) sites on the Internet is Facebook, where users communicate with their friends, join to groups, create groups, play games, and make friends around the world. Also, the vast number of groups are created for different causes and beliefs. However, overwhelming number of groups in one category causes difficulties for users to select a right group to join. To solve this problem, we introduce group recommendation system (GRS) using combination of hierarchical clustering technique and decision tree. We believe that Facebook SN groups can be identified based on their members’ profiles. Number of experiment results showed that GRS can make 73% accurate recommendation.
Keywords: decision tree; recommendation system; Social network

Privacy Management for Facebook - Baatarjav, Enkh-Amgalan; Ram Dantu; Phithakkitnukoon, Santi (4th International Conference on Information Systems Security (ICISS 2008), 2008)
As more people adopt the Internet as a medium of communication, the Internet has developed into a virtual world and this has resulted in many online social networks (SN). MySpace and Facebook, two leading online SN sites, have a combined user base of 170 million as of 2008. SN sites started to offer developers open platforms that provide users’ profile information to the developers. Unfortunately, the applications can also be used to invade privacy and to harvest the users’ profile information without their acknowledgement. To address this vulnerability, we propose a privacy-management system that protects the accessibility of users’ profile. The system uses probabilistic approach based on information revelation of users. Our experimental result shows that the system can achieve high accuracy rate of 75%.
Keywords: Facebook; Privacy; Privacy management; Social network